A survey on NiTi rotary instruments usage by endodontists and general dentist in Tehran - Mozayeni, Mohammadali; Golshah, Amin; Nik Kerdar, Nafiseh (Iranian Endodontic Journal, 2012)
INTRODUCTION: The aim of this study was to assess the extent of adoption, application and the associated issues with the nickel-titanium (NiTi) rotary instruments and techniques amongst endodontists and general dentists in Tehran. MATERIALS & METHODS: A total of 33 questions classified in six categories of demographics, frequency rate of NiTi rotary instrumentation and information. The sample size comprised of 100 endodontists and 100 general dental practitioners in Tehran. RESULTS: The overall response rate was 73.5%. NiTi rotary instruments were used by 98.4% and 50.6% of endodontists and general dentists, respectively. The main mentioned reason for not using rotary NiTi instruments was "lack of education". Among all procedural faults with NiTi, the most prevalent was “intra-canal file fracture” (88.5%) followed by "apical transportation" (71.2%) and "ledging" (68.3%). The main factors associated with the first procedural accident were "over-use" and “excessive pressure”. CONCLUSION: Dentists need more training and more comprehensive education regarding NiTi rotary instruments and techniques.